The Relationship Between Ante Natal Care Compliance With The Selection Of Birth Attendants In Pematang Tengah Village, Pematang Jaya District. Langkat - Domaria; Bagusda Kelana Putra; Indah Rahmaini Hayat; Dewi Andini (Institute of Computer Science (IOCS), 2018)
One of the goals of the ANC examination is to prepare women for childbirth (NICE, 2012). Childbirth readiness is the initial planning and preparation for childbirth that aims to help women, husbands and families to be ready for childbirth by making plans to deal with complications and unexpected things. Childbirth readiness can be assessed at six levels, namely the individual level of women, husband or family, environment, health workers, health facilities and policies. At the individual level, pregnant women and their husbands can prepare for childbirth and deal with complications by recognizing the danger signs that indicate complications that threaten the life of mother and baby, identifying trained birth attendants and delivery sites, providing savings and arranging transportation, while at the family and environmental level can identify donors. A woman who has prepared the six elements of labor readiness described by WHO is categorized as ready and vice versa if she prepares less than the six elements of labor readiness is categorized as not ready. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.002 at df = 1 where sig < (0.003 < 0 0.05) it can be seen that there is a relationship between ante natal care compliance with the selection of birth attendants in Pematang Tengah Village, Pematang Jaya District, Kab. Langkat Year 2018.